Integrasi Nilai Budaya dan Karakter Bangsa Melalui Implementasi Model VCT Tipe Examploritori Pada Mata Kuliah Pendidikan IPS di Prodi Pendidikan Sejarah FKIP UNSRI - Sani Safitri; Adhitya Rol Asmi (Sriwijaya University in collaboration with Perkumpulan Program Studi Pendidikan Sejarah Se-Indonesia (P3SI) dan Masyarakat Sejarawan Indonesia (MSI)., 2017)
This study aims to create, apply, and revise the integration of lifestyle model VCT Exparloritori type in the course of IPS Education in Prodi History Education. The research method used is model development). The development of the model used is a modified ASSIST model with formative evaluation of Tessmer through stages: (1) analysis of student characteristics, (2) determination of learning objectives, (3) material selection, methods and media, (4) SAP product products and teaching materials Based on VCT model Examploritori type learning and evaluation tools of cultural values and character of the nation through self evaluation, exspert riview, one-on-one, small group and field test. Data collection using interview technique, observation, documentation and questionnaire. Results developed for the development of VCT models examploritori type Products resulting from this development are SAP and teaching materials and measuring tools of cultural values and character of the nation. The results show that the learning model developed is valid by the expert as a validator, practically after being followed up by one to one evaluation and small group activities and also having potential impact on the cultural values and character of the nation. After field test or field test.pada student semester 1 force 2016/2017 History Study Program History FKIP UNSRI Palembang class.